2015
DOI: 10.1177/155698451501000301
|View full text |Cite
|
Sign up to set email alerts
|

Design Concepts and Preclinical Results of a Miniaturized HeartWare Platform: The MVAD System

Abstract: Objective: Ventricular assist device (VAD) miniaturization is one design trend that may result in less-invasive implantation techniques and more versatility with patient selection. The MVAD System is a miniature, continuous-flow device implanted in the ventricle. The pump is capable of delivering between 0 and 7 L/min of flow at a mean arterial pressure of 75 mm Hg. The impeller was optimized from its original design to improve hydraulic performance, minimize shear regions, and enhance the impeller's radial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…Apart from the development of pediatric VADs in current cardiac surgery, miniaturization of VADs designed for adult patients has been actively pursued . Decreased weight and size leads to increases in patients' mobility and reduces the degree of invasiveness and the time spent by the patient in clinic post‐implantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the development of pediatric VADs in current cardiac surgery, miniaturization of VADs designed for adult patients has been actively pursued . Decreased weight and size leads to increases in patients' mobility and reduces the degree of invasiveness and the time spent by the patient in clinic post‐implantation.…”
mentioning
confidence: 99%
“…Small size and short integrated inflow cannula allow for pericardial placement of the MVAD pump. Ovine model chronic studies demonstrated excellent biocompatibility and hemocompatibility of the MVAD pump . Another VAD being miniaturized for pediatric patients is the low‐shear pulsatile TORVAD system (Windmill Cardiovascular Systems, Inc, Austin, TX, USA).…”
mentioning
confidence: 99%
“…As far as we know, all the previous animal studies on VAD development did not induce heart failure before VAD implantation. 3,[13][14][15] The fact that the VAD is implanted in hearts with normal dimension also has an important implication to the selection of animal size to choose for the study. We used the Barbado sheep, with a weight of approximately 20 to 30 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Renal infarction occurs frequently during long-term animal studies testing VADs. 14,15 In the absence of histologically confirmed renal intravascular thrombus, determining the etiology of such infarcts remains speculative. In this study, 7 of the 10 sheep had visible pale lesions in the kidneys consistent with old infarcts.…”
Section: Discussionmentioning
confidence: 99%
“…A potentially optimized version of the HVAD pump has already been produced by HeartWare, termed MVAD and is currently being tested preclinically (34,35). The MVAD pump is a continuous axial flow pump and similar to the HVAD, it possesses "contactless" impeller suspension technology, supporting a wide range of flow rates.…”
Section: Future Directionsmentioning
confidence: 99%